With a Hammer for My Heart : A Novel - Lyon, George Ella, 1949- (Book collections on Project MUSE., 2007)
""A rich tale of healing, redemption, and social responsibility.""--Publishers Weekly ""A compelling, skillfully told story?. Lyon's finest achievement."" -- Lexington Herald-Leader ""Lyon gives readers a story rich in precise, gorgeous language that glows like a sword on the forge and cuts as deep?. Tragedies old and new weave a tiny Kentucky town into the center of the universe."" -- Booklist (starred review) ""Lyon consistently reveals in her work an ability to render the peculiarities of the people and the places she knows best, while at the same time exploring concerns that lend her